(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In any organization, Human Resource Development plays a critical role because it is now recognized as part of the modern management structure. In banks, HRD is a must for employees’ overall growth. The overall banking sector situation in India has been modified by globalization, liberalization and privatization. So, the current scenario of HRD activities in Indian Banks needs to be examined. The paper highlights HRD principles and their relevance in the banking sector.